2020
DOI: 10.1016/j.plabm.2020.e00183
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care testing of (N-terminal pro) B-type natriuretic peptide for heart disease patients in home care and ambulatory care settings

Abstract: Objectives The role of point-of-care testing (POCT) out of hospital, especially in home care and ambulatory care settings, is an issue meriting further research. We reviewed studies reporting cardiovascular events as a result of the implementation of B-type natriuretic peptide or N-terminal pro B-type natriuretic peptide POCT (BNP/NT-proBNP POCT) for heart disease patients in the settings. Design Articles were searched via a PubMed engine until May 30, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…An overview of studies using NP testing at the point of care in the community showed favourable results on cardiovascular outcomes 29 . Our study findings add that access to NP testing in primary care had an impact on the number of objectified HF diagnoses and case finding but that the added value of having the result at the point of care did not outweigh the time investment of the POC test.…”
Section: Discussionmentioning
confidence: 56%
“…An overview of studies using NP testing at the point of care in the community showed favourable results on cardiovascular outcomes 29 . Our study findings add that access to NP testing in primary care had an impact on the number of objectified HF diagnoses and case finding but that the added value of having the result at the point of care did not outweigh the time investment of the POC test.…”
Section: Discussionmentioning
confidence: 56%
“…Assessments revealed that the diagnostic value of H-FABP POCT is rather meager and inferior to Troponin I/T POCT [ 27 , 28 ]. NT-proBNP POCT having been part during the previous survey as BNP POCT, has proven to result in earlier diagnosis, reduced hospitalizations, and seem to be cost-effective for diagnosing and controlling heart failure [ 29 , 30 ]. However, in our present study, this POCT was rarely known (18.9%) and rarely used (3.9% of GPs).…”
Section: Discussionmentioning
confidence: 99%
“…To determine NT-proBNP values, a trained ERN performed bedside POC by using a cobas h 232 analyzer (Roche Diagnostics, Mannheim, Germany) [ 21 , 33 , 34 ] in all of the patients included in the study. The age-adjusted Charlson comorbidity index (ACCI) was used to study comorbidities [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is considerable interest in assessing new ways of early identification of sepsis with the N -terminal probrain natriuretic peptide (NT-proBNP), which is one of the most promising candidates [ 20 ]. As a result of the ongoing development of portable, robust, and reliable POC testing, it is now possible to obtain multiple biomarkers at bedside, clearly assisting the EMS personnel in the decision-making process since the very beginning of prehospital care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%